Humic acid involved chelation of ZnO nanoparticles for enhancing mineral nutrition in plants. (July 2021) - Rahale, C. Sharmila; Lakshmanan, A.; Sumithra, M.G.; Kumar, E. Ranjith
Abstract: Humic acid has been used to study the chelation of ZnO nanoparticles to improve plant micronutrition. ZnO nanoparticles were prepared using the ball milling process, and the prepared nanoparticles were chelated with Humic acid (Biomolecule). ZnO nanoparticles and surface modified Humic acid blended ZnS nanoparticles were studied for their structural, morphological, optical, and particle stability. XRD, FTIR, and TEM were used to examine the structural parameters. Humic acid affects the crystallite size and surface morphology of ZnO nanoparticles. The stability of humic acid blended ZnO nanoparticles is higher (38.45 mV) than that of ZnO nanoparticles alone (32.3 mV). The Zn mineral nutrition in plants is improved by humic acid blended ZnO nanoparticles. Highlights: Humic acid has been used to study the chelation of ZnO nanoparticles to improve plant micronutrition. Humic acid affects the crystallite size and surface morphology of ZnO nanoparticles. Zn mineral nutrition in plants is improved by humic acid blended ZnO nanoparticles.